DAMPAK CITRA MEREK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA MOBIL TOYOTA KOTA MEDAN - Tigor Rhade Jaya Purba; Satria Agung Ariansyah Simanjuntak; Ydris Talenta Barus; Hommy Dorthy Ellyany Sinaga (Jurnal Riset Multidisiplin Edukasi, 2026)
This study explores the influence of brand image and word of mouth on the purchase decision of Toyota cars in Medan. A descriptive qualitative approach was employed using a case study of Toyota consumers who purchased vehicles within the past two years. Data were collected through in depth interviews, participant observation at dealerships and user communities, and documentation of promotional materials and customer testimonials. Data analysis was conducted thematically through data reduction, categorization, and source triangulation. The results indicate that a strong Toyota brand image—particularly in terms of reliability, after sales service, and resale value—serves as the primary foundation for preference formation. Positive word of mouth from social networks and user communities accelerates the decision process and reduces buyer uncertainty. Recommendations are offered to Toyota and its dealers to strengthen customer experience, facilitate communication among users, and proactively manage the brand narrative.